Impact of COVID-19 on Mitochondrial-Based Immunity in Aging and Age-Related Diseases - Ganji, Riya; Reddy, P. Hemachandra (Frontiers in Aging Neuroscience, 2021)
The coronavirus disease 2019 (COVID-19) is a deadly pandemic, immune compromised disease with no cure. The COVID-19 is caused by acute respiratory syndrome corona virus 2 (SARS-CoV-2) with a range of clinical symptoms, including cough, fever, chills, headache, shortness of breath, difficulty breathing, muscle pain, and a loss of smell or taste. Aged individuals with comprised immunity are highly susceptible to COVID-19 and the likelihood increases with age and with presence of comorbidities such as hypertension, diabetes mellitus, cardiovascular disease, or chronic obstructive pulmonary disease. Emerging evidence suggests that COVID-19 highjacks mitochondria of immune cells and replicates within the mitochondria and impairs mitochondrial dynamics leading to cell death. Mitochondria are the power houses of the cell and largely involved in maintaining cell immunity, homeostasis and cell survival/death. Increasing evidence suggests that mitochondria from COVID-19 infected cells are highly vulnerable and vulnerability increases with age. The purpose of our article is to summarize the role of various age-related comorbidities such as diabetes, obesity, and neurological diseases in increasing mortality rates amongst the elderly with COVID-19. Our paper also highlights the interaction between coronavirus and mitochondrial dynamics in immune cells. We also highlight the current treatments, lifestyles, and safety measures that can help protect against COVID-19. Further research is urgently needed to understand the molecular mechanisms between mitochondrial virus and disease progression in COVID-19 patients.